Drifting Effect of Electrons on Ion Acoustic Waves in an Unmagnetized Quantum Plasmas - R. Kumar (International Journal of Mathematics And its Applications, 2022)
Both supersonic (mach number $M>1$) and subsonic ($M<1$) compressive solitary waves of high amplitudes are shown to exist in this plasma for quantum mechanical effects of electrons. Consideration of electron inertia facilitating its drift motion and quantum effects are responsible to the growth of high amplitude solitary waves. Highly energetic plasma particles are trapped in the pseudopotential of great depths under the quantum effects to result much higher amplitude compressive solitons.